Effects of Acupressure on Lactation: An Integrated Review. Issue 6 (November 2022) - Rosetti, Miriam A.; Spatz, Diane L.
Abstract: Purpose: To assess the effects of acupressure on lactation. Methods: A literature search was conducted via Cumulative Index to Nursing and Allied Health Literature (CINAHL), Embase, and PubMed using keyword search terms acupuncture, Tuina and breastfeeding, human lactation or human milk and excluded auricular . Inclusion criteria were articles in English with no restriction on publication date. We included acupuncture as well as acupressure to ensure that relevant articles were not missed. Results: After duplicates were removed, our initial search yielded 217 articles. Using the PRISMA checklist (Liberati et al., 2009 ), six articles met inclusion criteria (five research studies, one case study). Preliminary evidence suggests acupressure offers a promising and inexpensive method of enhancing secretory activation following cesarean and vaginal term and late preterm births, specifically when performed at acupoints CV 17, ST 18, and SI 1. Clinical Implications: Human milk is the optimal source of infant nutrition. Concern of low milk supply is most often cited as the cause for early supplementation with formula as well as early cessation of breastfeeding. Acupressure may be helpful in improving milk supply in early postpartum, but more research on acupressure and lactation is warranted. Abstract : Insufficient milk supply is a common reason for new mothers to stop breastfeeding. In this integrated review of the literature, studies on the effects of acupressure on lactation are reviewed. More evidence is needed, however, based on these results, acupressure may be a promising, inexpensive method of enhancing secretory activation during the early days postpartum that perinatal clinicians can learn.